Белый бакен: стихи / С. П. Зяблицев - Зяблицев Сергей Петрович (Удмуртия, 1988)
Экземпляры: ХР (20171016) / Инвентарный номер: 20207 / Цена: 0.20 / Сис.шифр: С(Удм)2 / Авт.знак: З-99 / ГРНТИ: 17 / ББК: 84(2Рос.Удм)^VLBC/RL